An assessment of hydrodynamic and simulated race performance features of three C-1 hull designs - Robinson, M. G.; Holt, L. E.; Pelham, T. W. (Human Movement, 2013)
Recently engineered Canadian Single (C-1) canoe hull designs have been found to produce less resistive drag than the traditional Delta design in tow tank test conditions. If these laboratory findings were found to be similar to on-water performance tests, then these new hull designs could give canoe sprint athletes a competitive advantage. However, these claims have not been independently confirmed nor has it been shown that these new designs result in improved performance under race conditions. Three C-1 hull designs (traditional Delta and the recently engineered Armageddon and Ergo-Starlight) were compared in order to detect differences in C-1 boat dynamics. Methods. The C-1 canoes were propelled by eleven national- and international-class paddlers who performed 350-m all-out trials from a dead start in each of the three crafts. One-way ANOVA compared differences in means for individual 50-meter segment and 350-meter performance times. Results. Performance times over the 350-meter race simulations were significantly faster (p = 0.038) among international-class paddlers with the Armageddon and Ergo-Starlight designs compared with the Delta. Conclusions. International level canoeists should expect improved performance times by choosing the Armageddon and Ergo-Starlight versus the Delta-designed C-1.